Culturing of Cryopreserved Stromal Cells on Carbon Microfibers - Petrenko, Yu. A.; Gurin, I. V.; Petrenko, A. Yu.; Sandomirsky, B. P. (Problems of Cryobiology and Cryomedicine, 2008)
There were investigated the stromal cell properties during culturing on carbon microfibers. It has been shown during application of carbon material with comparatively bigger radius of fibers any significant changes in metabolic activity of stromal cells at a combined culturing were not found out. The cells attached and spread on the surfaces of carbon fibers, enabled the proliferation, filling volumes among fibers and hereafter the formation of mono- and multiple layers. So, the carbon micrifibers are perspective material for development of bioengineered constructs of conjunctive tissue.